Performance of Angora rabbits on various vegetable proteins incorporated diets - BHATT, R S (The Indian Journal of Animal Sciences, 2014)
An experiment was conducted on 45 German Angora for 225 days. Experimental diets (S) were prepared by using soyaflakes (T1), sunflower-cake (T2), mustard-cake (T4) as a source of protein. Lysine and methionine were supplemented @ 100g / q in sunflower-cake (T3) and mustard- cake (T5) based diets. The level of rice - phak was added to adjust equal level offibre in all the diets. The fibre fraction except ADF and cellulose was lowered in the sunflower-cake and mustardcake added diets. The body weight decreased (P